Human attitudes towards herpetofauna: The influence of folklore and negative values on the conservation of amphibians and reptiles in Portugal - Ceríaco Luis MP (BMC, 2012)
Abstract Background Human values and folklore of wildlife strongly influence the effectiveness of conservation efforts. These values and folklore may also vary with certain demographic characteristics such as gender, age, or education. Reptiles and amphibians are among the least appreciated of vertebrates and are victims of many negative values and wrong ideas resulting from the direct interpretation of folklore. We try to demonstrate how these values and folklore can affect the way people relate to them and also the possible conservation impacts on these animals. Methods A questionnaire survey distributed to 514 people in the district of Évora, Portugal, was used to obtain data regarding the hypothesis that the existence of wrong ideas and negative values contributes to the phenomenon of human-associated persecution of these animals. A structural equation model was specified in order to confirm the hypothesis about the possible relationships between the presence of perceptions and negative values about amphibians and reptiles and persecution and anti-conservation attitudes. Sociodemographic variables were also added. Results The results of the model suggest that the presence of folklore and negative values clearly predicts persecution and anti-conservation attitudes towards amphibians and reptiles. Also, the existence of folklore varies sociodemographically, but negative values concerning these animals are widespread in the population. Conclusions With the use of structural equation models, this work is a contribution to the study of how certain ideas and values can directly influence human attitudes towards herpetofauna and how they can be a serious conservation issue.